SOME FACTORS THAT AFFECT TRANSFER PRICING DECISION - Resa Pide Pratama Septiyani; Wita Ramadhanti; Yudha Aryo Sudibyo (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2018)
The objectives of this research is to analyze the effect of tax minimization, firm size, foreign ownership bonus mechanism, and exchange rate on transfer pricing decision in multinational company engaged in manufacturing that listed on Indonesia Stock Exchange from the year of 2015 to 2016. Sampling method in this study is using purposive sampling using 8 criterias that have been determined. The result of binary regression analysis shows that only tax minimization that has positive effect on transfer pricing decision. While the others variable which are, firm size, foreign ownership, bonus mechanism, and exchange rate do not has an effect on transfer pricing decision.